4,4′-methylenediphenol reduces Aβ-induced toxicity in a Caenorhabditis elegans model of Alzheimer’s disease - Yu, Xingzhi; Tao, Jie; Xiao, Tian; Duan, Xiaohua (Frontiers in Aging Neuroscience, 2024)
Introduction Gastrodia elata Blume is a widely used medicinal and edible herb with a rich chemical composition. Moreover, prescriptions containing Gastrodia elata are commonly used for the prevention and treatment of cardiovascular, cerebrovascular, and aging-related diseases. Recent pharmacological studies have confirmed the antioxidant and neuroprotective effects of Gastrodia elata, and, in recent years, this herb has also been used in the treatment of Alzheimer’s disease (AD) and other neurodegenerative disorders. We have previously shown that 4,4′-methylenediphenol, a key active ingredient of Gastrodia elata, can mitigate amyloid-β (Aβ)-induced paralysis in AD model worms as well as prolong the lifespan of the animals, thus displaying potential as a treatment of AD. Methods We investigated the effects of 4,4′-methylenediphenol on AD and aging through paralysis, lifespan, and behavioral assays. In addition, we determined the anti-AD effects of 4,4′-methylenediphenol by reactive oxygen species (ROS) assay, lipofuscin analysis, thioflavin S staining, metabolomics analysis, GFP reporter gene worm assay, and RNA interference assay and conducted in-depth studies on its mechanism of action. Results 4,4′-Methylenediphenol not only delayed paralysis onset and senescence in the AD model worms but also enhanced their motility and stress tolerance. Meanwhile, 4,4′-methylenediphenol treatment also reduced the contents of reactive oxygen species (ROS) and lipofuscin, and decreased Aβ protein deposition in the worms. Broad-spectrum targeted metabolomic analysis showed that 4,4′-methylenediphenol administration had a positive effect on the metabolite profile of the worms. In addition, 4,4′-methylenediphenol promoted the nuclear translocation of DAF-16 and upregulated the expression of SKN-1, SOD-3, and GST-4 in the respective GFP reporter lines, accompanied by an enhancement of antioxidant activity and a reduction in Aβ toxicity; importantly, our results suggested that these effects of 4,4′-methylenediphenol were mediated, at least partly, via the activation of DAF-16. Conclusion We have demonstrated that 4,4′-methylenediphenol can reduce Aβ-induced toxicity in AD model worms, suggesting that it has potential for development as an anti-AD drug. Our findings provide ideas and references for further research into the anti-AD effects of Gastrodia elata and its active ingredients.